Indicadores da qualidade da bacia hidrográfica para gestão integrada dos recursos hídricos. Estudo de caso: Bacia hidrográfica do Médio Tocantins (TO) - Tundisi, José Eduardo Matsumura (2006)
In this thesis a diagnosis of the conditions the watershed of the Middle Tocantins river was carried out with the objective to develop a management plan for the area of influence of the reservoir of the hydroelectric power plant, Luiz Eduardo Magalhães. The power plant started its operation in 2002. The diagnosis of the water quality of the reservoir and its tributaries was made with the objective to understand the relationships quality of the watershed / water quality as a response of impacts and conservation areas. The Middle Tocantins watershed has 13 sub-basins. In this work 4 sub-basins were selected, two heavily impacted (Ribeirão da Água Fria e Córrego São João) and two with low impacts (Rio Lajeado and Ribeirão São João). The quality of the sub-basins was obtained evaluating the condition and vulnerability of the watershed. To characterize the watershed condition the indicator used was the state of conservation (percentage of original vegetation cover, agricultural areas, urbanization, wetlands preserved). Limnological, physical, chemical and biological analysis of the reservoir, both in short periods of time with real time monitoring and seasonally was performed in order to analyses the dynamics of the system and its response to external and internal inputs. Hydrodynamics of the reservoir was analyzed in order to understand processes of vertical and horizontal circulation and their interaction with the eutrophication of the reservoir. Nutrient enrichment due to agricultural and urban wastes is one of the main problems of the degradation of water quality. The results show that from the four sub-basins analyzed, the two heavily impacted, Ribeirão da Água Fria and Córrego São João, have the greatest percentage of areas of human activity (56- 61%) with 36-41% of preserved original vegetation and wetlands. The two less impacted watersheds, (Ribeirão do Lajeado e Ribeirão São João) presented another percentage: 54-56% of preserved areas and 41-44% of impacted areas. Demographic expansion, urbanization and intensive soil use is the main cause of the increase of eutrophication of the reservoir. The trophic state index applied to the reservoir showed that its trophic states ranges from oligotrophy to mesotrophy. This could be probably due to the short retention time of the reservoir (25 days) and the less intensive use and occupation of the watersheds. A management plan was prepared considering the risk areas and the environmental zoning altogether with the reservoir dynamics. The aim of this plan (risk analysis for eutrophication and sediment transport and input) is to provide a tool for decision makers to develop a process of integrated, predictive and the watershed level of management in order to optimize multiple uses.